2022
DOI: 10.1002/slct.202103674
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized MCM‐41: Versatile Catalysts for Organic Transformations

Abstract: Functionalized MCM-41 constitute a group of potent hybrid catalysts for organic reactions. Their pore size is large enough to house large substrate molecules, the large bulk of surface silanol groups helps in introduction of a variety of functionalities required for the catalytic action. The current review emphasizes the broad methodology for the synthesis of these catalysts, effect of functionalization on reaction parameters, stability, efficiency, selectivity, reusability along with limitations of these cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 180 publications
(218 reference statements)
0
7
0
Order By: Relevance
“…However, it was found that efficient selectivity in epoxidation was achieved only with a low incorporation of Nb metal into the MCM-48 support. [29][30][31][32][33][34] Yan et al conducted research on MSM catalysts based on tungsten (W) and niobium (Nb) for the epoxidation of ethylene, utilizing hydrogen peroxide (H 2 O 2 ) as the oxidizing agent. 35 It was revealed that both W-KIT-6 and Nb-KIT-6 metal catalysts exhibited signicant efficiency in EO production under standard conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, it was found that efficient selectivity in epoxidation was achieved only with a low incorporation of Nb metal into the MCM-48 support. [29][30][31][32][33][34] Yan et al conducted research on MSM catalysts based on tungsten (W) and niobium (Nb) for the epoxidation of ethylene, utilizing hydrogen peroxide (H 2 O 2 ) as the oxidizing agent. 35 It was revealed that both W-KIT-6 and Nb-KIT-6 metal catalysts exhibited signicant efficiency in EO production under standard conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a pore system with a uniform size distribution and the ease of functionalization with both organic molecules and inorganic oxides or nanoparticles have allowed the development of a wide range of materials with the most diverse applications. 2 The pore size of MCM-41 limited its application, so other materials with larger pore sizes quickly appeared, such as SBA-15 or SBA-16. 3 Among the fields in which silica mesoporous materials have been used, we can mention catalysis, biomedicine, sensors, controlled release, etc .…”
Section: Introductionmentioning
confidence: 99%
“…[5] After removal of the template the MCM material class offers highly ordered mesopores, which allow e. g. the formation of nanoreactors in the pores. [6][7][8] Further due to mesoporosity (pore sizes between 2 to 50 nm), MCM materials provide very high surface area (up to 1500 m 2 g À 1 ), which is very promising for different fields of application like catalysis, [9][10][11][12][13][14] medicine, [15][16][17][18][19][20] proton conduction [21][22][23][24][25][26][27] or purification/adsorption processes [28][29][30][31][32] and immobilization processes, [33][34][35][36] like e. g. immobilization of catalysts. [37][38][39][40] Another very attractive characteristic of MCM materials is the fact that these materials consist only of silica (SiO 2 ), which is non-toxic for our body, so the application in and on our body is possible.…”
Section: Introductionmentioning
confidence: 99%